Provocative tests of anal sphincter function correlate with symptoms and subtypes of faecal incontinence - John McLaughlin; Dipesh H Vasant; Asbjørn Mohr Drewes; Abhiram Sharma; Matthew Davenport; Edward Kiff; Karen Telford; Alexander O'Connor; Donghua Liao; Niels Klarskov (BMJ Open Gastroenterology)
Objectives High-resolution anorectal manometry (HRAM) is the established investigation in faecal incontinence (FI). However, provocative tests (functional lumen imaging probe (FLIP) and anal acoustic reflectometry (AAR)) have been proposed as alternatives. This study uniquely explores all three methods in correlation with FI symptoms and subtypes.Methods This was a prospective observational study of patients with FI attending a tertiary pelvic floor unit between August 2022 and January 2024. Patients underwent HRAM, FLIP and AAR with the order randomised. FI severity was assessed with the Vaizey score and quality-of-life with the Manchester Health Questionnaire.Results 40 patients (39 women, median age: 62 (range: 38–85)) were recruited with 27 (67.5%) reporting urge FI, 8 (20%) mixed and 5 (12.5%) passive incontinence. FLIP squeeze measurements correlated with the Vaizey score, including incremental squeeze pressure at 40 mL (rs=−0.412; p=0.008) and 50 mL (rs=−0.414; p=0.009) and the pressure-diameter volume loop at 50 mL (rs=−0.402; p=0.011). Incremental squeeze opening pressure with AAR correlated with the Vaizey score (rs=−0.339; p=0.032). There was no correlation between symptom severity and HRAM parameters, or any parameter and quality-of-life scores. Resting parameters with all three modalities were lower in passive FI: mean resting pressure (HRAM; p=0.010), yield pressure (FLIP; p=0.031) and opening pressure (AAR; p=0.006). With FLIP, there was a trend towards reduced squeeze function in the urge group (pressure-diameter volume loop at 50 mL; p=0.295).Conclusions FLIP and AAR correlate better with FI symptoms compared with HRAM. Therefore, these provocative tests could be used to guide the management of FI in prospective studies.